Statistical arbitrage and risk management at AFC Capital Limited (AFCCL) - Saadi, Abrar Hassan (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.